Survival Strategy Pedagang Garmen Pasar Tradisional di Era Digital Dalam Perspektif Maqashid Syariah - Maziyah Mazza Basya; Alifiah Farizky (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to identify the survival mechanisms carried out by garment traders at the Darmo Trade Center Wonokromo Traditional Market in facing the challenges of the digital era using the perspective of maqashid sharia. The market transformation from conventional to digital has posed a major challenge for garment traders at the Darmo Trade Center Wonokromo Traditional Market to maintain their business, so a special strategy is needed in order to survive. This study uses a qualitative method with a case study approach. The study was conducted on 10 garment traders at the Darmo Trade Center Wonokromo Traditional Market. The results of this study indicate that the economic conditions of garment traders at the Darmo Trade Center Wonokromo Traditional Market are very unstable, so they adopt various strategies to survive in the online market era which include active strategies and passive strategies. The survival strategies carried out are in accordance with the objectives of maqashid sharia in an effort to maintain life (hifz Nafs) and maintain property (hifz Maal).